Epidemiology and nature of self-harm in children and adolescents: findings from the multicentre study of self-harm in England. - Hawton, K; Bergen, H; Waters, K; Ness, J; Cooper, J; Steeg, S; Kapur, N (2012)
We examined epidemiology and characteristics of self-harm in adolescents and impact of national guidance on management. Data were collected in six hospitals in three centres between 2000 and 2007 in the Multicentre Study of Self-harm in England. Of 5,205 individuals (7,150 episodes of self-harm), three-quarters were female. The female:male ratio in 10-14 year-olds was 5.0 and 2.7 in 15-18 year-olds. Rates of self-harm varied somewhat between the centres. In females they averaged 302 per 100,000 (95 % CI 269-335) in 10-14 year-olds and 1,423 (95 % CI 1,346-1,501) in 15-18 year-olds, and were 67 (95 % CI 52-82) and 466 (95 % CI 422-510), respectively, in males. Self-poisoning was the most common method, involving paracetamol in 58.2 % of episodes. Presentations, especially those involving alcohol, peaked at night. Repetition of self-harm was frequent (53.3 % had a history of prior self-harm and 17.7 % repeated within a year). Relationship problems were the predominant difficulties associated with self-harm. Specialist assessment occurred in 57 % of episodes. Self-harm in children and adolescents in England is common, especially in older adolescents, and paracetamol overdose is the predominant method. National guidance on provision of psychosocial assessment in all cases of self-harm requires further implementation.